Telecardiology system for fourth generation heterogeneous wireless networks - Yew, Hoe Tung; Yudha Aditya; Haikal Satrial; Eko Supriyanto; Yuan, Wen Hau (Asian Research Publishing Network, 2015)
Telecardiology allows healthcare professionals to monitor and interpret their patients’ electrocardiography (ECG) via information and communication technologies (ICT). It improves the cardiac patient’s life quality by bridging the gap between healthcare professionals and patients. With the rapid development of ICT, telecardiology systems now can support high quality medical image and video. However, the existing telecardiology systems are relying on a single wireless network. These systems are unable to guarantee that the users will be always connected to the wireless network. Furthermore, these systems are less reliable due to poor network quality will results an interruption on telecardiology application. Thus, a telecardiology system integrated with vertical handover algorithm for Fourth Generation (4G) heterogeneous wireless networks is proposed to compensate the imperfection of existing telecardiology systems. The proposed system allows users always connected to the best quality network at anytime and anywhere in seamless manner. The simulation result shows that the proposed system outperforms the existing telecardiology systems which rely on single network in term of network quality.